Survivorship and Modes of Failure of Varus-Valgus Constrained Implants in Revision Knee Arthroplasty: A Study with a Median Follow-Up of 2.9 Years in an Asian Population - Hirunyachoke, Paphon; Dorjiee, Gem; Nakbunnam, Rapeepat; Chareancholvanich, Keerati; Pornrattanamaneewong, Chaturong (Journal of Southeast Asian Orthopaedics, 2025)
Purpose: This study aims to evaluate the survival rate, primary causes of failure, and complications associated with varus-valgus-constrained (VVC) implants in revision total knee arthroplasty (TKA) at a large Asian medical institution. Methods: We retrospectively reviewed 161 patients who underwent revision TKA with VVC implants at our institution between January 2013 and December 2021. Data on patient demographics, initial diagnosis, revision dates, causes of failure, and subsequent re-revisions were collected and analyzed. The Kaplan-Meier method was used to estimate implant survival rates. Results: This study included 161 patients who received VVC implant revisions, with a mean age of 73 years at the time of surgery. The mean follow-up period was 2.9 years, extending up to 10.0 years. The primary reasons for revision were infection (47.8%), aseptic loosening (36%), and instability (8.1%). The overall survival rate of VVC implants was 86.3%, with aseptic revisions at 84.5% and septic revisions at 88.3%, based on a median follow-up of 2.9 years. The 2-year survival rates were 92.5% overall, 88.1% for aseptic revisions, and 97.4% for septic revisions. The re-revision rate was 13.7% (22 VVC implants), primarily due to infections (86.4%). Conclusions: VVC implants demonstrated a high 2-year survival rate of 92.5% in revision TKA at a large Asian medical institution. The most common indications for VVC implant use in revisions were infection and aseptic loosening, with infection being the leading cause of subsequent re-revisions.